Investigation of CCL1 rs159294 T/A gene polymorphism in pulmonary and extrapulmonary tuberculosis patients - Ozdemir, Fethi Ahmet; Erol, Deniz; Yuce, Hueyin; Konar, Vahit; Senli, Ebru Kara; Bulut, Funda; Deveci, Figen (Turkish Assoc Tuberculosis & Thorax, 2013)
Introduction: The purpose of this study is to reveal whether CCL1 rs159294 T/A polymorphism in pulmonary and extrapulmonary tuberculosis patients pose a risk to catch tuberculosis or not. Materials and Methods: In the study, peripheral blood samples from the control group, which includes 160 patients, who consulted to Firat University Faculty of Medicine, Pulmonology Policlinic in Elazig province and who were diagnosed with tuberculosis; and 160 healthy individuals, were taken and put into tubes containing EDTA. Each tube contained 2 cc blood samples. DNA isolation was made from these blood samples and CCL1 rs159294 T/A polymorphism was defined with PCR-RFLP analysis. Results: For CCL1 rs159294 T/A polymorphism, TT genotype was found in 98 (61.3%) patients, TA genotype was found in 58 (36.3%) patients, AA genotype was found in 4 (2.5%) patients among 160 patients with tuberculosis; and TT genotype was found in 50 (70.4%) patients, TA genotype in 20 (28.2%) patients, AA genotype was found in 1 (1.4%) patient among 71 patients with pulmonary tuberculosis; TT genotype was found in 48 (53.9%) patients TA genotype was found in 38 (42.7%) patients and AA genotype was found in 3 (3.4%) patients among 89 extrapulmonary tuberculosis patients. And in control group, among 160 healthy individuals, TT genotype was found in 100 (62.5%) individuals, TA genotype was found in 58 (36.3%) individuals, AA genotype was found in 2 (1.3%) individuals and no statistically significant difference was found. Conclusion: CCL1 rs159294 T/A polymorphism do not form an inclination to tuberculosis in our population.
Pulmoner ve ekstrapulmoner tüberküloz hastalari{dotless}nda CCL1 rs159294 T/A gen polimorfizminin araşti{dotless}ri{dotless}lmasi{dotless}
Keywords: Pulmonary tuberculosis; extrapulmonary tuberculosis; CCL1; polymorphism